Design of E-Assessment for Creative Thinking in Project-Based Learning on Colligative Properties of Solutions - Slamet Reza Nasrullah; Rr. Lis Permana Sari (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2025)
Assessment is an important part of the learning process in chemistry education, which requires conceptual understanding and creative thinking skills. However, traditional assessment often fails to accommodate the needs of 21st-century learning, which requires the integration of technology, creativity, and problem solving. This study aims to determine: (1) the characteristics of eAssessment, (2) the feasibility of e-Assessment on teacher usability tests, and (3) the student responses to e-Assessment on student readability tests. This study employed a Design-Based Research model. In this study, a product trial was conducted with 10 high school chemistry teachersand 36 grade XII high school students. Data analysis techniques used descriptive qualitative and quantitative methods to determine product quality based on ideal assessment criteria. Based on teacher evaluations, the product was rated very high, with average scores for content (22.70 out of 25.00), presentation (23.00 out of 25.00), usability (27.60 out of 30.00), and project learning (22.70 out of 25.00). Based on student readability, the scores were very high, with average scores for presentation (22.11 out of 25.00), language (9.11 out of 10.00), and attractiveness (16.78 out of 20.00). Thus, the developed e-Assessment system is deemed suitable for use by teachers as a student assessment system.